The Effectiveness of Mentoring Program towards Sunnah Worship Rituals of Muslim Students from Faculty of Psychology, UMS - Idris, Siti Rabiatul Adawiyah; Cahayani, Arindiar Kusuma; Asyanti, Setia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Globalization makes the world seem to have no boundaries anymore, brings big changes for Indonesian youth, namely global values that are incompatible with the superior values of the Indonesian people. scientifically qualified, but also has superior character and away from deviant behaviors that are not following the values of Islam. This research aimed to see whether the mentoring program was effective in increasing the sunnah worship rituals for students. The method used was a pre-experimental design with a pre-test-post-test one group design. The sampling technique used in this study was purposive sampling, by determining certain criteria that had been determined by researchers. The subjects were 48 female students from the Faculty of Psychology, Muhammdiyah Surakarta University. The results of this study stated that the mentoring program was not effective to improve the psychology rituals of female students. However, these results need to be interpreted carefully. There are some factors which likely to cause this condition: 1) mentoring activities that have not been optimal, both regarding the material, delivery methods and the role of the mentor. 2) behavioral change targets, namely ritual worship, 3) other outside variables that are influential but not yet controlled.